2016
DOI: 10.1177/0020872814537851
|View full text |Cite
|
Sign up to set email alerts
|

Challenges facing international social workers: English managers’ perceptions

Abstract: International labour mobility is occurring in social work and isolated studies are beginning to research this topic. This article reports on one aspect of research into the experiences of 'international social workers' (ISWs) in London (UK), namely, the perceptions of the managers who supervise them, with regards to their preparedness, induction and support needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
(58 reference statements)
0
7
1
Order By: Relevance
“…About 10 percent of the total number of social workers registered to practice in the UK completed their qualification abroad (Hussein et al, 2010). Hanna and Lyons (2016) highlight the importance of understanding the experiences of migrating social workers. This is the gap that this study hopes to fill by studying the migration of social workers from Australia, Canada, India, Ghana, Romania, South Africa, the United States and Zimbabwe to the United Kingdom.…”
Section: Introductionmentioning
confidence: 99%
“…About 10 percent of the total number of social workers registered to practice in the UK completed their qualification abroad (Hussein et al, 2010). Hanna and Lyons (2016) highlight the importance of understanding the experiences of migrating social workers. This is the gap that this study hopes to fill by studying the migration of social workers from Australia, Canada, India, Ghana, Romania, South Africa, the United States and Zimbabwe to the United Kingdom.…”
Section: Introductionmentioning
confidence: 99%
“…The social work profession strives to improve individuals' and families' quality of life as well as uplift and contribute towards functional communities and promote social justice. The unfriendly behaviour reported in the finding is based on the attitude of the co-workers and it further shows that, even though social workers are trained to fight social injustices, no environment is safe from hostile behaviour and oppression (Hanna & Lyons, 2014;Wojczewski et al, 2015). Indeed, knowingly and/or unknowingly, social workers themselves can be perpetrators of the same injustices they are supposed to be fighting and such perceptions can explicitly or subtly find their way into policies (Roestenburg, 2013).…”
Section: "I Have Seen In Terms Of Language Barriers As I Highlightedmentioning
confidence: 81%
“…A later study by Hanna and Lyons (2014) looked at European social workers practising in England and highlighted the "local realities" that social workers are expected to intervene in, yet their training might not have entirely provided for that. This study by Hanna and Lyons (2014) built on a study by Pullen-Sansfacon, Brown and Graham's research (2012a), which emphasised the importance of understanding professional and context-specific adaptation processes of international social workers.…”
Section: Transnational/ International Social Workmentioning
confidence: 99%
“…There is now an extensive literature on the increasing mobility of social workers in Aotearoa New Zealand, as noted earlier, and in the United Kingdom (Hanna & Lyons, 2014;Hatzidimitriadou & Psoinos, 2017;Hussein, 2014;Hussein et al, 2011;Moriarty, Hussein, Manthorpe, & Stevens, 2012;Tinarwo, 2015;Zanca & Misca, 2016); Ireland (Walsh, Wilson, & O'Connor, 2010); Australia (Harrison, 2013;Papadopoulos, 2017Papadopoulos, 2018Zubrzycki, Thomson, & Trevithick, 2008;Modderman, Threlkeld, & McPherson, 2017); Canada (Brown, Sansfaçon, Éthier, & Fulton, 2014;Fulton, Pullen Sansfaçon, Brown, Éthier, & Graham, 2016;Pullen Sansfaçon, Brown, Graham, & Dumais Michaud, 2013). More recently, research has been published that has reported on the experiences of migrant workers in the United States (Lin, Chiang, Lux, & Lin, 2018), Zimbabwean social workers in South Africa (Mangena & Warria, 2017) and of Latin American social workers in Switzerland (Bolzman, 2015).…”
Section: Literaturementioning
confidence: 81%